The Synthesis of Zeolites A, X and HS from Natural Iranian Kaolinite and the Study of the Transformation of Zeolites X to HS and Zeolites Y to P by X-ray diffraction and Scanning Electron Microscopy. (Journal of Sciences, Islamic Republic of Iran)
Zeolites A, X and HS were synthesized from natural Iranian Kaolinite by alkaline fusion,,followed by refluxing the mixture. The transformation of zeolites X to HS and Y to P were studied at different time intervals by X-ray diffraction and Scanning Electron Microscopy (SEM). It was revealed that in solution, zeolites HS and P are more stable than zeolites X and Y respectively